Silicon dioxide composite abrasive with hydrophilic core-shell structure, preparation method of silicon dioxide composite abrasive and application of silicon dioxide composite abrasive in chemical mechanical polishing

By preparing SiO2@PMMA composite abrasive, the problems of scratches and low polishing efficiency on silicon wafer surfaces were solved, achieving high-efficiency and low-cost silicon wafer polishing results.

CN121046033APending Publication Date: 2025-12-02SHANGHAI INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511213224.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing abrasives suffer from problems such as scratches on silicon wafer surfaces, low polishing efficiency, and insufficient dispersion stability of polishing slurry during the polishing process.

Method used

A hydrophilic core-shell composite abrasive with SiO2 as the core and polymethyl methacrylate (PMMA) as the shell was developed. SiO2 microspheres were prepared by template method, and MMA was polymerized on the SiO2 surface using silane coupling agent and initiator to form PMMA layer. Plasma hydrophilic treatment was then used to improve dispersibility.

Benefits of technology

It reduces silicon wafer scratches while improving polishing rate and efficiency, and the manufacturing process is simple and inexpensive, making it suitable for chemical mechanical polishing of silicon wafers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121046033A_ABST
    Figure CN121046033A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon dioxide composite abrasive with a hydrophilic core-shell structure and a preparation method and application of the silicon dioxide composite abrasive in chemical mechanical polishing, the silicon dioxide composite abrasive is composed of SiO2 serving as a core and polymethyl methacrylate wrapping the periphery of the SiO2, the particle size of the SiO2 ranges from 100 nm to 300 nm, and the particle size of the composite abrasive ranges from 200 nm to 350 nm. The preparation method comprises the following steps: preparing SiO2 microspheres by using a template agent and a silicon source through a template method, taking the SiO2 microspheres as an inner core of a core-shell structure, enabling the silicon spheres to be hydrophobic by using a modifier, introducing double bonds through a silane coupling agent, adding MMA and an initiator, adding a PMMA outer layer on the surface of the silicon spheres, and synthesizing the composite abrasive SiO2 coated PMMA with a hydrophilic core-shell structure after hydrophobic modification. Compared with the prior art, the composite abrasive can be used as a chemical polishing solution for chemical polishing of silicon wafers, scratches on the silicon wafers are reduced, and meanwhile the polishing rate and efficiency can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor materials technology, and in particular to a hydrophilic core-shell structured silica composite abrasive, its preparation method, and its application in chemical mechanical polishing. Background Technology

[0002] Semiconductors are the core of the modern electronics industry and have a profound impact on global economic and technological development. Semiconductor silicon is the most important functional material in the semiconductor industry and the number one functional electronic material. Silicon is a hard and brittle material with a diamond crystal structure and atoms bonded by covalent bonds. Its hardness reaches 1000 HV, but its fracture strength is very low. Machining such a hard and brittle material with ultra-precision is quite difficult.

[0003] Currently, common abrasives such as SiO2 exhibit good selectivity and dispersibility, resulting in good mechanical wear performance. However, it can lead to scratches on the silicon wafer surface and is prone to gelation in the polishing slurry. CeO2 abrasives have good stability and are less prone to scratches on the silicon wafer surface, but because Ce is a rare earth element, its cost is relatively high, its preparation process is relatively complex, requiring precise control of its particle size, morphology, and distribution, and its polishing rate is slow. Al2O3 abrasives, due to their high hardness and strength, have good wear resistance, but the problem of scratches on the silicon wafer surface is still quite serious. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems of surface scratches, polishing efficiency, and insufficient dispersion stability of polishing fluid in existing traditional abrasives, thereby providing a hydrophilic core-shell structured silica composite abrasive, its preparation method, and its application in chemical mechanical polishing.

[0005] In this invention, SiO2 is used as the core, and composite abrasives synthesized with alumina, polystyrene, and polymethyl methacrylate as shells are compared. Finally, polymethyl methacrylate (PMMA), an organic glass that is softer than inorganic abrasives, is selected as the shell to form the SiO2@PMMA composite abrasive system. This reduces scratches on silicon wafers during polishing without reducing the polishing rate and effect, and may even improve the polishing rate and effect. Moreover, the synthesized SiO2@PMMA composite abrasive system has a simple process and low cost. The selected modifier can solve the problem of SiO2 agglomeration. Furthermore, a silane coupling agent containing double bonds is introduced to enable PMMA to be well grafted onto the outer layer of each SiO2. The SiO2@PMMA composite abrasive is hydrophobically modified to ensure stable dispersion in the polishing fluid.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a hydrophilic core-shell structured silica composite abrasive, which is composed of SiO2 as the core and polymethyl methacrylate wrapped around its periphery, wherein the particle size of SiO2 is 100nm-300nm and the particle size of silica composite abrasive is 200nm-350nm.

[0008] The second technical solution of the present invention is to provide a method for preparing a silica composite abrasive with a hydrophilic core-shell structure as described in one of the above technical solutions, comprising the following steps:

[0009] S1. Add silicon source and precipitant to template agent to react and obtain SiO2 microspheres;

[0010] S2. The SiO2 microspheres obtained in step S1 and the modifier are heated and reacted in an organic solvent to obtain dispersed SiO2 microspheres;

[0011] S3. Disperse the dispersed SiO2 microspheres obtained in step S2 in a solvent, add a silane coupling agent and heat to react, add methyl methacrylate (MMA) and an initiator, and continue to heat to react under an inert atmosphere to obtain a core-shell structured silica composite abrasive.

[0012] S4. Treat the silica composite abrasive obtained in step S3 with a plasma hydrophilic treatment device or add the silica composite abrasive to a solvent containing a surfactant to obtain a silica composite abrasive with a hydrophilic core-shell structure.

[0013] In some specific embodiments, in step S1, the template agent is selected from any one of dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), octadecyltrimethylammonium bromide (OTAB), hexadecyltrimethylammonium bromide (CTAB), soybean lecithin, egg yolk lecithin, sodium cholate, and sodium deoxycholate.

[0014] The silicon source is selected from any one of tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, and polyethyl orthosilicate.

[0015] The precipitant is selected from any one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, sodium phosphate, ethylenediamine, triethylamine, pyridine, tetramethylammonium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, formic acid, citric acid, sodium chloride, ammonium chloride, and ammonium sulfate.

[0016] In some specific embodiments, in step S2, the modifier is selected from any one of allyltrimethoxysilane, n-octyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, epoxysilane, vinyltrimethylsilane, sodium stearate, stearic acid, and oleic acid.

[0017] The organic solvent is selected from either anhydrous ethanol or ethyl acetate.

[0018] In some specific embodiments, in step S3, the solvent is selected from any one of water, alcohol, ethyl acetate, acetone, and toluene;

[0019] The silane coupling agent is selected from any one of methacryloyloxytrimethoxysilane (KH570), acryloyloxypropyltrimethoxysilane (ACMO), allyltrimethoxysilane, allyltriethoxysilane, vinyldimethylethoxysilane, and undecenyltrimethoxysilane.

[0020] The initiator is selected from any one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), benzoyl peroxide (BPO), dicumyl peroxide (DCP), diisopropyl peroxide dicarbonate (IPP), potassium persulfate (KPS), aluminum trichloride, boron trifluoride, tantalum pentachloride, n-butyllithium, and potassium amino.

[0021] In some specific embodiments, in step S4, the surfactant is selected from any one of Tween 20, Tween 40, Tween 80, polyethylene glycol 4000, polyethylene glycol 5000, Span 20, Span 40, Span 60, Span 80, and Span 85;

[0022] The solvent is selected from any one of water, alcohol, ethyl acetate, acetone, and toluene.

[0023] In some specific embodiments, in step S1, the ratio of the amount of template agent, silicon source and precipitant is (0.5-1)g:(5-15)mL:(1-5)mL.

[0024] In some specific embodiments, in step S1, the reaction temperature is 40-50°C and the time is 6-8 hours.

[0025] In some specific embodiments, in step S2, the mass ratio of SiO2 microspheres to modifier is (0.5-2.5):(0.1-0.3).

[0026] In some specific embodiments, in step S2, the temperature of the heating reaction is 50-70°C, and the heating reaction time is 2-4 hours.

[0027] In some specific embodiments, in step S3, the mass ratio of the dispersed SiO2 microspheres, silane coupling agent, methyl methacrylate and initiator is (0.3-2.5):(0.2-0.6):(1.2-2.4):(0.05-0.1).

[0028] In some specific embodiments, in step S3, the temperature of the heating reaction is 70-90°C, and the total heating reaction time is 8-12 hours.

[0029] In some specific embodiments, in step S4, the gas used in the plasma hydrophilic treatment equipment to treat the silica composite abrasive is selected from any one of O2, Ar, and N2, with a discharge power of 0-150W and a time of 15-30min.

[0030] In some specific embodiments, in step S4, the mass ratio of surfactant to silica composite abrasive is (0.5-2.0):(1.0-5.0).

[0031] The third technical solution of this invention provides an application of a hydrophilic core-shell structured silica composite abrasive, as described in one of the above technical solutions, in the chemical mechanical polishing of silicon wafers. It is primarily used in the ultra-precision polishing process of single-crystal silicon wafers, and is particularly suitable for polishing silicon wafers with strict requirements for surface roughness, material removal rate, and surface damage control.

[0032] In some specific embodiments, the application includes the preparation of chemical mechanical polishing slurries.

[0033] In some specific embodiments, the chemical mechanical polishing slurry comprises the following components by mass percentage:

[0034] 0.2-9% hydrophilic core-shell structured silica composite abrasive;

[0035] 0.2-9% oxidant;

[0036] 0.05-5% dispersant;

[0037] 0.05-5% complexing agent;

[0038] 0.001-0.5% corrosion inhibitor;

[0039] 0.01-2% surfactant;

[0040] The remainder is solvent.

[0041] In some specific embodiments, the oxidant is selected from any one or more of hydrogen peroxide, nitric acid, periodic acid, persulfate, ozone, sodium hypochlorite, ferric nitrate, and peracetic acid;

[0042] The dispersant is selected from any one or more of polyvinylpyrrolidone (PVP), polyacrylic acid (PAA) and its salts, polyethylene glycol (PEG), modified cellulose, and organic amine dispersants;

[0043] The complexing agent is selected from any one or more of triethanolamine, citric acid and its salts, disodium ethylenediaminetetraacetate (EDTA), aminocarboxylic acid salts, hydroxycarboxylic acid salts, polyacrylamide, and sodium aminotriacetate;

[0044] The corrosion inhibitor is selected from any one or more of benzotriazole (BTA), imidazoline compounds, alkyl alcohol amines, silicates, boric acid and its salts, and polyethylene oxide (PEO);

[0045] The surfactant is selected from any one or more of sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (SDBS), hexadecyltrimethylammonium chloride, dodecyl dimethyl benzyl ammonium chloride (DDAB), polyoxyethylene ether (PPOE), and polyoxyethylene alkyl ether (AEO).

[0046] In some specific embodiments, the pH of the chemical mechanical polishing slurry is adjusted to 7-9.5 in the chemical mechanical polishing process, and the polishing process conditions include: polishing pressure of 0.5-3.5 psi, polishing pads made of polyurethane, nylon, or velvet, sample tray rotation speed of 50-100 r / min, polishing tray rotation speed of 80-150 r / min, polishing slurry feed flow rate of 50-150 mL / min, and polishing time of 5-10 min.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) This invention uses a template method to prepare SiO2 microspheres. A modifier is used to solve the problem of SiO2 microsphere agglomeration. Furthermore, a silane coupling agent containing double bonds and an initiator are introduced to allow MMA to better polymerize on the surface of each SiO2 microsphere, forming a PMMA layer. The SiO2@PMMA composite abrasive with a hydrophilic core-shell structure prepared by this invention consists of a layer of softer PMMA coated on the outer layer of hard SiO2. The synthesized abrasive is hydrophilically modified so that it can be well dispersed in the polishing slurry during silicon wafer polishing, reducing scratches on the silicon wafer while ensuring polishing rate and efficiency.

[0049] (2) The preparation process of this invention is simple and low in cost. The synthesized abrasive has uniform coating, good monodispersity, and good polishing effect. It can be used in the chemical mechanical polishing of silicon wafers. Attached Figure Description

[0050] Figure 1 The image shows a scanning electron microscope (SEM) image of the SiO2 microspheres prepared in Example 1.

[0051] Figure 2 Scanning electron microscope image of the modified SiO2 microspheres prepared in Example 1.

[0052] Figure 3 The contact angle is that of the modified SiO2 microspheres prepared in Example 1.

[0053] Figure 4 The image shows a scanning electron microscope (SEM) image of the SiO2@PMMA composite microspheres prepared in Example 1.

[0054] Figure 5 Thermogravimetric analysis (TGA) of the SiO2@PMMA composite microspheres prepared in Example 1.

[0055] Figure 6 The contact angle of the SiO2@PMMA composite microspheres prepared in Example 1.

[0056] Figure 7 The image shows the dynamic light scattering pattern of the SiO2@PMMA composite microspheres prepared in Example 1.

[0057] Figure 8 The images show the XRD patterns of the SiO2 microspheres, modified SiO2 microspheres, and SiO2@PMMA composite microspheres prepared in Example 1.

[0058] Figure 9 The infrared spectra of the SiO2 microspheres and SiO2@PMMA composite microspheres prepared in Example 1 are shown.

[0059] Figure 10 The image shows the dynamic light scattering pattern of the modified SiO2@PMMA composite microspheres prepared in Example 1.

[0060] Figure 11 The contact angle of the modified SiO2@PMMA composite microspheres prepared in Example 1.

[0061] Figure 12 White light image showing the polishing effect of modified SiO2@PMMA composite microspheres on silicon wafers.

[0062] Figure 13 White light image showing the polishing effect of modified SiO2@PS composite microspheres on silicon wafers.

[0063] Figure 14 White light image showing the polishing effect of modified SiO2@Al2O3 composite microspheres on silicon wafers. Detailed Implementation

[0064] This invention provides a method for preparing a hydrophilic core-shell structured silica composite abrasive, comprising the following steps:

[0065] S1. Add silicon source and precipitant to template agent in batches and small amounts to carry out reaction, and obtain SiO2 microspheres after centrifugation, washing and drying;

[0066] S2. The SiO2 microspheres obtained in step S1 and the modifier are heated and reacted in an organic solvent. After centrifugation, washing and drying, dispersed SiO2 microspheres are obtained.

[0067] S3. The dispersed SiO2 microspheres obtained in step S2 are dispersed in a solvent, a silane coupling agent is added and heated to react, methyl methacrylate (MMA) and an initiator are added, and the reaction is continued under an inert atmosphere. After centrifugation, washing and drying, a core-shell structured silica composite abrasive is obtained.

[0068] S4. Treat the silica composite abrasive obtained in step S3 with a plasma hydrophilic treatment device or add the silica composite abrasive to a solvent containing a surfactant to obtain a silica composite abrasive with a hydrophilic core-shell structure.

[0069] Preferably, in step S1, the template agent is selected from any one of dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), octadecyltrimethylammonium bromide (OTAB), hexadecyltrimethylammonium bromide (CTAB), soybean lecithin, egg yolk lecithin, sodium cholate, and sodium deoxycholate.

[0070] The silicon source is selected from any one of tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, and polyethyl orthosilicate.

[0071] The precipitant is selected from any one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, sodium phosphate, ethylenediamine, triethylamine, pyridine, tetramethylammonium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, formic acid, citric acid, sodium chloride, ammonium chloride, and ammonium sulfate.

[0072] Preferably, in step S2, the modifier is selected from any one of allyltrimethoxysilane, n-octyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, epoxysilane, vinyltrimethylsilane, sodium stearate, stearic acid, and oleic acid.

[0073] The organic solvent is selected from either anhydrous ethanol or ethyl acetate.

[0074] Preferably, in step S3, the solvent is selected from any one of water, alcohol, ethyl acetate, acetone, and toluene;

[0075] The silane coupling agent is selected from any one of methacryloyloxytrimethoxysilane (KH570), acryloyloxypropyltrimethoxysilane (ACMO), allyltrimethoxysilane, allyltriethoxysilane, vinyldimethylethoxysilane, and undecenyltrimethoxysilane.

[0076] The initiator is selected from any one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), benzoyl peroxide (BPO), dicumyl peroxide (DCP), diisopropyl peroxide dicarbonate (IPP), potassium persulfate (KPS), aluminum trichloride, boron trifluoride, tantalum pentachloride, n-butyllithium, and potassium amino.

[0077] Preferably, in step S4, the surfactant is selected from any one of Tween 20, Tween 40, Tween 80, polyethylene glycol 4000, polyethylene glycol 5000, Span 20, Span 40, Span 60, Span 80, and Span 85.

[0078] The solvent is selected from any one of water, alcohol, ethyl acetate, acetone, and toluene.

[0079] Preferably, in step S1, the ratio of the amount of template agent, silicon source, and precipitant is (0.5-1)g:(5-15)mL:(1-5)mL.

[0080] Preferably, in step S1, the reaction temperature is 40-50℃ and the time is 6-8h.

[0081] Preferably, in step S1, the centrifugation speed is 7000-12000 r / min and the time is 3-15 min;

[0082] The washing process involves using alcohol and water.

[0083] The drying temperature is 50-75℃, and the time is 12-24 hours.

[0084] Preferably, in step S2, the mass ratio of SiO2 microspheres to modifier is (0.5-2.5):(0.1-0.3).

[0085] Preferably, in step S2, the temperature of the heating reaction is 50-70°C, and the heating reaction time is 2-4 hours.

[0086] Preferably, in step S2, the centrifugation speed is 7000-12000 r / min and the time is 3-15 min;

[0087] The washing process involves using alcohol and water.

[0088] The drying temperature is 50-75℃, and the time is 12-24 hours.

[0089] Preferably, in step S3, the mass ratio of the dispersed SiO2 microspheres, silane coupling agent, methyl methacrylate, and initiator is (0.3-2.5):(0.2-0.6):(1.2-2.4):(0.05-0.1).

[0090] Preferably, in step S3, the temperature of the heating reaction is 70-90°C, and the total heating reaction time is 8-12 hours.

[0091] Preferably, in step S3, the centrifugation speed is 7000-12000 r / min and the time is 3-15 min;

[0092] The washing process involves using alcohol and water.

[0093] The drying temperature is 50-75℃, and the time is 12-24 hours.

[0094] Preferably, in step S4, the gas used in the plasma hydrophilic treatment equipment to treat the silica composite abrasive is any one of O2, Ar, or N2, with a discharge power of 0-150W and a time of 15-30min.

[0095] Preferably, in step S4, the mass ratio of surfactant to abrasive is (0.5-2.0):(1.0-5.0).

[0096] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0097] Unless otherwise specified, the raw materials or processing techniques used in the following embodiments and comparative examples are all conventional commercially available raw materials or conventional processing techniques in the art.

[0098] Example 1

[0099] This embodiment provides a SiO2@PMMA composite abrasive with SiO2 as the core and polymethyl methacrylate as the shell. The preparation method includes the following steps:

[0100] (1) Disperse 0.8g of the template agent cetyltrimethylammonium bromide (CTAB) in a three-necked flask containing 100mL of deionized water and 50mL of ethanol solvent, and sonicate for 30min to obtain solution A;

[0101] (2) Dissolve 10 mL of tetraethyl orthosilicate in 30 mL of ethanol until fully dissolved to obtain solution B;

[0102] (3) Add 10 mL of solution B to solution A, react at 45 °C for 10 min, then add 1.5 mL of ammonia and 10 mL of solution B. Add solution B and ammonia in small amounts several times until solution B is completely added and a total of 4.5 mL of ammonia is added. React at 45 °C for 7 h, centrifuge at 7500 r / min for 10 min, wash three times with water and three times with ethanol, and dry at 60 °C for 12 h to obtain SiO2 microspheres;

[0103] (4) Dispersion experiment of SiO2 microspheres: 1.2g of SiO2 microspheres were dissolved in 200mL of anhydrous ethanol, sonicated for 30min, and then 0.24g of hexadecyltrimethoxysilane was added. After stirring and heating at 70℃ for 3h, the mixture was centrifuged at 7500r / min for 10min, washed three times with water and three times with ethanol, and dried at 60℃ for 12h to obtain dispersed modified SiO2 microspheres.

[0104] (5) Grafting experiment of modified SiO2 microspheres: 0.8g of modified SiO2 microspheres were ultrasonically dispersed in 100mL of ethyl acetate and 0.48g of KH570 was added. After reacting at 70℃ for 5h, an ethyl acetate solution containing 4g of methyl methacrylate and 0.2g of azobisisobutyronitrile was added. Azobisisobutyronitrile can be dissolved in a small amount of acetone before adding ethyl acetate. The reaction was stirred at 80℃ for 10h under nitrogen protection, centrifuged at 7500r / min for 10min, washed three times with water and ethanol, and dried at 60℃ for 24h to obtain SiO2@PMMA composite abrasive.

[0105] (6) The SiO2@PMMA composite abrasive was subjected to hydrophilic treatment. The prepared abrasive was placed in a plasma hydrophilic treatment device, O2 was introduced, the discharge power was 100w, and the reaction time was 30min to obtain the modified SiO2@PMMA composite abrasive.

[0106] like Figure 1 The image shown is a scanning electron microscope image of the SiO2 microspheres prepared in steps (1), (2), and (3). It can be seen that the particle size of the synthesized silica is about 250 nm, and the agglomeration is severe. The contact angle was measured to be 14.959°, which indicates that the prepared silica is highly hydrophilic and has severe agglomeration, which is not conducive to the uniform coating of PMMA.

[0107] like Figure 2 and 3 The image shows a scanning electron microscope (SEM) image and contact angle of the modified SiO2 microspheres after treatment with the modifier in step (4). It can be seen that the silica microspheres are dispersed and the contact angle is measured to be 125.882°, indicating that the silica microspheres have a significant dispersion effect and that each silica microsphere can be uniformly coated with PMMA.

[0108] like Figure 4 ,5 Tables 6, 7, and 1 show the scanning electron microscope (SEM) images, thermogravimetric (TGA) images, contact angles, and dynamic light scattering (FLRS) images of the SiO2@PMMA composite abrasive prepared in this embodiment. It is evident that the outer layer of silica has a significant coating material. The mass reduction in mass from 100℃ to 400℃ is equal to the mass of PMMA. The contact angle is 142.713°, indicating successful synthesis of SiO2@PMMA (particle size <10μm). However, it is hydrophobic. Table 1 shows that its polydispersity index (PDI) in water is 0.5468, indicating poor dispersibility in water. Since the polishing slurry uses water as a solvent, further modification is needed to obtain a hydrophilic material to improve its dispersion in the polishing slurry.

[0109] Table 1. Polydispersity Index (PDI) of SiO2@PMMA Composite Abrasives

[0110]

[0111] like Figure 8 and 9 The image shows the XRD patterns of SiO2, modified SiO2, and SiO2@PMMA composite microspheres, and the infrared spectrum of SiO2 and SiO2@PMMA composite microspheres. It can be seen that at 1720 cm⁻¹... -1 and 1100cm -1 The peak value indicates that C=O bonds and Si-O-Si bonds coexist.

[0112] like Figure 10 , 11 Table 2 shows the contact angle and dynamic scattering diagram of the modified SiO2@PMMA composite microspheres obtained after hydrophilic treatment in step (6). It can be seen that the contact angle after hydrophilic modification is 38.124° and the polydispersity index (PDI) is 0.09684, indicating that the dispersion effect in water is better than that before modification.

[0113] Table 2. Polydispersity Index (PDI) of Modified SiO2@PMMA Composite Microspheres

[0114]

[0115] Example 2:

[0116] The modified SiO2@PMMA composite abrasive prepared in Example 1 was used to prepare a polishing slurry, including the following steps:

[0117] 2g of modified SiO2 / PMMA composite abrasive, 1wt% hydrogen peroxide (as oxidant), 0.6wt% polyvinylpyrrolidone (as dispersant), 0.5wt% triethanolamine (as complexing agent), 0.01wt% benzotriazole (as corrosion inhibitor), 0.1wt% sodium dodecyl sulfate (as surfactant), and water as solvent were mixed with sodium hydroxide to adjust the pH to 9 to obtain 100mL of polishing solution.

[0118] Comparative Example 1:

[0119] Compared with Example 1, most of them are the same, except that "methyl methacrylate (MMA)" in step (5) is replaced with styrene to prepare modified SiO2@PS composite abrasive.

[0120] The polishing slurry was prepared according to the steps of Example 2, specifically by replacing "modified SiO2 / PMMA composite abrasive" with "modified SiO2@PS composite abrasive".

[0121] Comparative Example 2:

[0122] Compared with Example 1, most of them are the same, except that methyl methacrylate in step (5) is replaced with alumina to prepare modified SiO2@Al2O3 composite abrasive.

[0123] The polishing slurry was prepared according to the steps of Example 2, specifically by replacing "modified SiO2 / PMMA composite abrasive" with "modified SiO2@Al2O3 composite abrasive".

[0124] The polishing slurries prepared in Example 2, Comparative Example 1, and Comparative Example 2 were subjected to polishing experiments to test their performance.

[0125] The polishing experiment was conducted as follows: A 20mm*20mm silicon wafer was placed on an aluminum alloy sample block. The grinding disc rotation speed was set to 30 rpm, and deionized water was delivered using an automatic dropper. 400#, 600#, 1000#, and 1200# Si-CMP sandpaper were used sequentially to mechanically grind the surface of the silicon wafer for 3 minutes to remove surface roughness defects. Then, the prepared polishing slurry was added, and a polyurethane polishing pad was used with a pressure of 0.5 psi for 10 minutes of polishing.

[0126] like Figure 12 , 13Figures 1 and 14 show the white light images of the polishing effects of modified SiO2@PMMA, modified SiO2@PS, and modified SiO2@Al2O3 on silicon wafers, respectively. It can be seen that the surface of modified SiO2@PMMA is significantly flatter, and the surface roughness (Ra) after polishing is 12.702nm, 0.386μm, and 0.154μm, respectively, indicating that modified SiO2@PMMA has a better polishing effect.

[0127] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A hydrophilic core-shell structured silica composite abrasive, characterized in that, It consists of a core of SiO2 and a surrounding polymethyl methacrylate, wherein the particle size of the SiO2 is 100nm-300nm and the particle size of the silica composite abrasive is 200nm-350nm.

2. A method for preparing a hydrophilic core-shell structured silica composite abrasive as described in claim 1, characterized in that, Includes the following steps: S1. Add silicon source and precipitant to template agent to react and obtain SiO2 microspheres; S2. The SiO2 microspheres obtained in step S1 and the modifier are heated and reacted in an organic solvent to obtain dispersed SiO2 microspheres; S3. Disperse the dispersed SiO2 microspheres obtained in step S2 in a solvent, add a silane coupling agent and heat to react, add methyl methacrylate and an initiator, and continue heating to react under an inert atmosphere to obtain a core-shell structured silica composite abrasive. S4. Treat the silica composite abrasive obtained in step S3 with a plasma hydrophilic treatment device or add the silica composite abrasive to a solvent containing a surfactant to obtain a silica composite abrasive with a hydrophilic core-shell structure.

3. The preparation method according to claim 2, characterized in that, In step S1, the template agent is selected from any one of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, soybean lecithin, egg yolk lecithin, sodium cholate, and sodium deoxycholate. The silicon source is selected from any one of tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, and polyethyl orthosilicate. The precipitant is selected from any one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, sodium phosphate, ethylenediamine, triethylamine, pyridine, tetramethylammonium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, formic acid, citric acid, sodium chloride, ammonium chloride, and ammonium sulfate. In step S2, the modifier is selected from any one of allyltrimethoxysilane, n-octyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, epoxysilane, vinyltrimethylsilane, sodium stearate, stearic acid, and oleic acid; The organic solvent is selected from either anhydrous ethanol or ethyl acetate; In step S3, the solvent is selected from any one of water, alcohol, ethyl acetate, acetone, and toluene; The silane coupling agent is selected from any one of methacryloyloxytrimethoxysilane, acryloyloxypropyltrimethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, vinyldimethylethoxysilane, and undecenyltrimethoxysilane; The initiator is selected from any one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dicumyl peroxide, diisopropyl peroxide, diisopropyl peroxide, potassium persulfate, aluminum trichloride, boron trifluoride, tantalum pentachloride, n-butyllithium, and potassium amino. In step S4, the surfactant is selected from any one of Tween 20, Tween 40, Tween 80, polyethylene glycol 4000, polyethylene glycol 5000, Span 20, Span 40, Span 60, Span 80, and Span 85. The solvent is selected from any one of water, alcohol, ethyl acetate, acetone, and toluene.

4. The preparation method according to claim 2, characterized in that, In step S1, the ratio of the amount of template agent, silicon source, and precipitant is (0.5-1)g:(5-15)mL:(1-5)mL; The reaction temperature is 40-50℃ and the reaction time is 6-8 hours.

5. The preparation method according to claim 2, characterized in that, In step S2, the mass ratio of SiO2 microspheres to modifier is (0.5-2.5):(0.1-0.3); The heating temperature for the reaction is 50-70℃, and the heating time is 2-4 hours.

6. The preparation method according to claim 2, characterized in that, In step S3, the mass ratio of the dispersed SiO2 microspheres, silane coupling agent, methyl methacrylate, and initiator is (0.3-2.5):(0.2-0.6):(1.2-2.4):(0.05-0.1). The heating temperature is 70-90℃, and the total heating time is 8-12 hours.

7. The preparation method according to claim 2, characterized in that, In step S4, the gas used in the plasma hydrophilic treatment equipment to process the silica composite abrasive is selected from any one of O2, Ar, and N2, with a discharge power of 0-150w and a time of 15-30min.

8. The preparation method according to claim 2, characterized in that, In step S4, the mass ratio of surfactant to silica composite abrasive is (0.5-2.0):(1.0-5.0).

9. The application of a hydrophilic core-shell structured silica composite abrasive as described in claim 1 in the chemical mechanical polishing of silicon wafers.

10. The application according to claim 9, characterized in that, The hydrophilic core-shell structured silica composite abrasive is used to prepare a chemical mechanical polishing slurry, which is composed of the following components by mass percentage: 0.2-9% hydrophilic core-shell structured silica composite abrasive; 0.2-9% oxidant; 0.05-5% dispersant; 0.05-5% complexing agent; 0.001-0.5% corrosion inhibitor; 0.01-2% surfactant; The remainder is solvent.

Citation Information

Cited By

  • High-transparency neutral silicone adhesive and preparation method thereof

    CN121873738A